microRNA-430b targets scavenger receptor class B member 1 (scarb1) and inhibits coloration and carotenoid synthesis in koi carp (Cyprinus carpio L.) - Tian, Xue; Peng, Nian-nian; Ma, Xiao; Wu, Li-min; Shi, Xi; Liu, Hui-fen; Song, Hong-mei; Wu, Qi-sheng; Meng, Xiao-lin; Li, Xue-jun (Aquaculture, 2022)
In teleost fishes, miR-430 has several paralogs and is widely required for mesoderm formation and gonad development. However, the functions of miR-430 in skin pigmentation have not been completely elucidated. To understand the functions of miR-430 in color formation, we analyzed the conserved characteristics of miR-430 family in teleost, detected miR-430 family spatial and temporal expression patterns, verified the target differences between miR-430a and miR-430b, identified the phenotypic changes by overexpressing miR-430b in vivo and assessed the roles of miR-430b in coloration by analyzing the genes associated with pteridine and carotenoid pigment metabolism. The results showed that miR-430a and miR-430b were highly conserved in teleosts and that miR-430b was intensively expressed in skin, fins and scales comparing with miR-430a. Target verification analysis showed that miR-430b displayed significant repressive effects on scarb1 compared with miR-430a. In addition, overexpression of miR-430b led to diminished red intensity by decreasing skin carotenoid content and xanthophores/erythrophores density in scales. Accompanying the color dilution, the mRNA and protein levels of scarb1 were markedly inhibited by increased miR-430b, and several genes correlated with carotenoid metabolism also underwent corresponding modification. However, the contents of pteridine pigments and related genes experienced only limited changes. These findings suggest that miR-430b can improve skin pigmentation by blocking the expression of scarb1, resulting in carotenoid metabolism dysregulation and chromatophores density reduction. •miR-430b exhibited different evolution and expression pattern from miR-430a.•Overexpression miR-430b in vivo led to color lightening and chromatophores reduction.•miR-430b contributed to carotenoids dysregulation by inhibiting scarb1 expression.•Overexpression miR-430b rarely functioned in pteridines metabolism and related genes.